Organización Contable en la Empresa Industrial Empacadora de Materiales Reciclables “IEMAR-REIPAP” del Sr. Pintado Narváez Víctor Manuel de la ciudad de Loja, periodo del 01 de abril al 30 de junio del 2023 - Pintado Ramos, María Elizabeth (2023)
The present Work of Curricular Integration denominated Accounting Organization in the Industrial Company Packing Recyclable Materials "IEMAR-REIPAP" of Mr. Pintado Narváez Víctor Manuel from the city of Loja, period from April 1 to June 30, 2023, was developed with the purpose of providing a comprehensive vision of the economic and financial situation of the company through the results obtained as a result of the accounting process implemented. To meet the stated objectives, an analysis was carried out on the direction and nature of the business, which allowed the preparation of the Account Plan and Manual based on the specific activities of the company to facilitate the recording of economic events; consequently, the main and auxiliary formats were designed, including commercial and cost accounting records, such as compaction auxiliaries, cardex cards, time cards, clock cards, payment and provision rolls, purchase and sale auxiliaries, among others, allowing an effective organization of the data and providing detailed information on economic movements; subsequently, the data was collected, classified and recorded using the source documents as a basis, therefore, the Initial Inventory was prepared by physically verifying the assets, values or rights, allowing the Initial Situation Statement to be obtained, and accounting entries were made in the Daily Ledger to record the economic activities, the General Ledger was then prepared by classifying the accounting accounts and the corresponding codes, facilitating the preparation of the Trial Balance with their respective amounts and balances, and the Worksheet with the necessary adjustments, as a result the Financial Statements were obtained as of June 30, 2023, which present the following values, the Statement of Financial Position showed total Assets of $287,627.66, Liabilities of $43,555.37 and Equity of $244,072.30, which increased due to the profit generated in the fiscal year, in relation to the Statement of Income, there was a total Income of $90,813.68, Costs of $59,805.92 and Expenses of $19. 741.15, obtaining a profit for the year of $11,266.61. The Cash Flow Statement showed a net cash flow of $9,328.92, and the Statement of Cost of Product Sold determined the total value of the compacted material, showing a cost of product sold of $52,172.04. Finally, once the Curricular Integration Work was completed, we proceeded with the elaboration of the conclusions and recommendations, which will support the development, growth and decision making relevant to the company.